2020
DOI: 10.3390/ijms21072389
|View full text |Cite
|
Sign up to set email alerts
|

Effective Cellular Transport of Ortho-Halogenated Sulfonamide Derivatives of Metformin Is Related to Improved Antiproliferative Activity and Apoptosis Induction in MCF-7 Cells

Abstract: Metformin is a substrate for plasma membrane monoamine transporters (PMAT) and organic cation transporters (OCTs); therefore, the expression of these transporters and interactions between them may affect the uptake of metformin into tumor cells and its anticancer efficacy. The aim of this study was to evaluate how chemical modification of metformin scaffold into benzene sulfonamides with halogen substituents (compounds 1–9) may affect affinity towards OCTs, cellular uptake in two breast cancer cell lines (MCF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
(55 reference statements)
2
9
0
Order By: Relevance
“…Among OCT transporters, OCT3 were predominant in MDA-MB-231 cells, while in the case of MCF-7, we were not able to detect any of OCT transporters. In the case of MATE transporters similar significant expression of MATE 1 in both cell lines was reported [ 26 ]. These results are in agreement with outcomes of Cai et al [ 19 ] who also concluded that there is a relationship between the presence of cation-selective transporters, the effectiveness of metformin uptake and its antiproliferative activity.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…Among OCT transporters, OCT3 were predominant in MDA-MB-231 cells, while in the case of MCF-7, we were not able to detect any of OCT transporters. In the case of MATE transporters similar significant expression of MATE 1 in both cell lines was reported [ 26 ]. These results are in agreement with outcomes of Cai et al [ 19 ] who also concluded that there is a relationship between the presence of cation-selective transporters, the effectiveness of metformin uptake and its antiproliferative activity.…”
Section: Resultssupporting
confidence: 73%
“…The first step of the studies included establishing a relationship between cytotoxic effects of the examined compounds and their cellular uptake in MCF-7 and MDA-MB-231 cells. Both examined cell lines were previously characterized according to the expression of OCT, PMAT and MATE transporters [ 26 ]. Among OCT transporters, OCT3 were predominant in MDA-MB-231 cells, while in the case of MCF-7, we were not able to detect any of OCT transporters.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Metformin has been commonly used for treatment of patients with diabetic mellitus worldwide because of higher values of clinical efficacy, safety, and cost [ 78 ]. In addition to antidiabetic functions, biguanides have been reported to possess antineoplastic effects in various types of malignant tumors, such as cervical cancer, breast cancer, and pancreatic neuroendocrine tumors [ 79 , 80 , 81 ]. The associated anticancer mechanisms involve cell signaling molecules such as FAK, Akt, Rac1, RhoA, cyclin D1, and proliferating cell nuclear antigen [ 79 , 81 ].…”
Section: Chemical Compoundsmentioning
confidence: 99%